Strategy to Improve the Quality of Islamic Educational Institutions Through the Child-Friendly School Model Based on Adiwiyata - Suwandi Suwandi; Triyo Supriyatno (Abjadia, 2021)
The quality of education is a pillar of human resource development which is very important for national development. The child friendly school program is one of the efforts made to improve the quality of madrasas. This research is important because so far, the quality of education has been studied only on aspects of learning related to the academic field which have an impact on certain aspects. The purpose of this study was to find out and understand the strategy in improving the quality of education in Madrasah Ibtidaiyah Negeri 3 Jombang through the child friendly school program based on Adiwiyata. In addition, to find out the impact or implication of the implementation of the child friendly school program on the quality of education. This study uses a descriptive qualitative approach with a case study design. Data collection techniques were carried out by means of in-depth interviews, participant observation, and documentation. The data analysis was carried out with the process of data collection, data coding, data classification, data reduction, and data exposure. The results showed that the strategy carried out included several stages, namely: Formation of the implementing team for child friendly school, Conducting program socialization, Fostering human resources (teachers and staff), Building collaboration, Fulfilling indicators for child friendly school components, Carrying out monitoring and evaluation processes, and Responsive to inputs for the improvement of the child friendly school program. The implications of the program on the quality of education are seen in three aspects, namely teachers, students and institution.